Debt as a (credible) collusive device, or: "Everybody happy but the consumer" - Giancarlo Spagnolo (Fondazione Eni Enrico Mattei (FEEM), 1999)
The paper proposes a theory of the anti-competitive effects of debt finance based on the interaction between capital structure, managerial incentives, and firms' ability to sustain collusive agreements. It shows that shareholders' commitments that reduce conflicts with debtholders such as hiring managers with valuable reputations or "conservative" incentives besides reducing the agency costs of debt finance also greatly facilitate tacit collusion in product markets. Concentrated or collusive credit markets, or large banking groups, can ensure the credibility of such commitments (renegotiation-proofness), thereby "exporting" collusion through leverage in otherwise competitive downstream product markets.
Keywords: D21; G32; L13; L41; 330; Banks; oligopoly; financial market product market interaction; capital structure; managerial incentives; collusion; governance; Wettbewerbsbeschränkung; Kapitalstruktur; Oligopol; Führungskräfte; Anreizvertrag; Theorie